Isovitexin targets SIRT3 to prevent steroid-induced osteonecrosis of the femoral head by modulating mitophagy-mediated ferroptosis - Yinuo Fan; Zhiwen Chen; Haixing Wang; Mengyu Jiang; Hongduo Lu; Yangwenxiang Wei; Yunhao Hu; Liang Mo; Yuhao Liu; Chi Zhou; Wei He; Zhenqiu Chen (Bone Research)
Abstract The death of osteoblasts induced by glucocorticoid (GC)-mediated oxidative stress plays a crucial role in the development of steroid-induced osteonecrosis of the femoral head (SIONFH). Improving bone formation driven by osteoblasts has shown promising outcomes in the prognosis of SIONFH. Isovitexin has demonstrated antioxidant properties, but its therapeutic effects on GC-induced oxidative stress and SIONFH remain unexplored. In this study, we analyzed clinical samples obtained from SIONFH patients using proteomic and bioinformatic approaches. We found an imbalance in mitochondrial homeostasis and ferroptosis-induced impairment of osteogenic capacity in SIONFH. Subsequently, we investigated the cause-and-effect relationship between mitochondria and ferroptosis, as well as the regulatory role of mitophagy in maintaining mitochondrial homeostasis and controlling ferroptosis. We then identified the critical involvement of SIRT3 in modulating mitochondrial homeostasis and ferroptosis. Furthermore, molecular docking and co-immunoprecipitation confirmed the strong interaction between SIRT3 and BNIP3. Strikingly, restoring SIRT3 expression significantly inhibited pathological mitophagy mediated by the BNIP3/NIX pathway. Additionally, we discovered that Isovitexin, by promoting SIRT3 expression, effectively regulated mitophagy, preserved mitochondrial homeostasis in osteoblasts, suppressed ferroptosis, and restored osteogenic capacity, leading to remarkable improvements in SIONFH. These findings reveal the effects and molecular mechanisms of Isovitexin on SIONFH and highlight the potential of targeting SIRT3 as a promising strategy to suppress mitophagy-mediated ferroptosis in osteoblasts and against SIONFH.